Photo receiver with nanocluster subsystem - Kovalchuk, Volodymyr V. (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
The paper considers the effects associated with a change in the properties of a film heterojunction as a result of the introduction of a nanocluster subsystem. Such a modified heterojunction exhibits a spectrally invertible photo ventile effect. A design of a photocell containing two successively coupled p-n transitions of counter action, photoactive in different regions of the spectrum, is proposed.